Konsep Fitrah dalam Perspektif Islam dan Komparasinya dengan Konsep Tabula Rasa - Tanjung, Zainal Syari Yanti; Hanafiah, Muhammad Ali; Fadhilah, Muthia Nur (AUD Cendekia: Journal of Islamic Early Childhood Education, 2025)
This study originates from the need to understand the nature of humanity through two major concepts: fitrah in Islam and tabula rasa in Western philosophy. Both address the initial condition of human beings and the roles of innate disposition and environmental influence in moral, intellectual, and spiritual development. The aim of this research is to describe the concept of fitrah from the Islamic perspective, explain the tabula rasa concept within the tradition of Western empiricism, and compare both in the context of human development and their implications for education. This study employs a qualitative method with a library research approach, analyzing primary sources such as the Qur’an, Hadith, classical Islamic works, and the writings of empiricist thinkers such as John Locke, David Hume, and Jean-Jacques Rousseau. The findings indicate that fitrah represents the innate human potential inclined toward monotheism and goodness, whereas tabula rasa asserts that humans are born without innate ideas and are shaped entirely by experience. The comparative analysis reveals that both concepts converge in emphasizing the importance of education and experience, yet differ in their theological and epistemological orientations. The implications of this research highlight the necessity for holistic education that nurtures the innate spiritual potential of human beings while also considering the influence of environment and experience in character formation.